One Size Doesn't Fit All: Diversifying research on active labor market policies - Sophie Danneris (Social Work & Society, 2016)
Over several decades, there has accumulated a large body of research on active labor market policies (ALMP). In particular, numerous programs designed to encourage welfare recipients to move into work and off benefits have been evaluated in western countries such as Denmark. The results of the research have been selectively influential in shaping policy developments, but as this paper will demonstrate, there are several biases attached to this research. Based on an extensive mapping review of both Danish and international literature, this paper contributes with a systematic overview of the current research within the field. By focusing on the range of these studies (in design, populations covered and substantive issues addressed), the review looks beyond the specific results of each study, and illuminates substantial gaps in the knowledge produced. The analysis shows that the research is lacking sensitivity toward the complexity of the field, in particular regarding the diversity of the clients being served and the variety of challenges they confront.